(3OaY GdCTcGd aj eSGMI GdCTcGds - (3CHh YHO Gddg jYjT Hf EHQGgje Hf jhSa Hf SeGc, GdCehj GdGfOdS,J (B900 (3g` s ((3Ndjd Hf CMeO GdeOGHZi GdTHQGhi s)
(3ChdgG (B:s
(3GdeSGMI JLRFIGdTF GdeLghd eYdhe s
(3BNQgG (B:s
(3hGdMeO ddg Ydi eG CLRd ef LRjd YWGFg s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B53 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdHdOjI HGdGScfOQjI (B(5174) s
Keywords: (3GdQjGVjGJs